New method and indicators for measuring inclusiveness of value chain upgrading - CGIAR Research Program on Rice (2020)
The method has been piloted on a case study of participation in contract farming by rice farmers in Vietnam. The method can be used by policy makers to assess inclusiveness of rice value chain upgrading. The method has been used to assess inclusiveness of consumer access to food safety.